2020
DOI: 10.5187/jast.2020.62.5.638
|View full text |Cite
|
Sign up to set email alerts
|

Substitution effects of rice for corn grain in total mixed ration on rumen fermentation characteristics and microbial community in vitro

Abstract: This study determined the substitution effects of rice for corn as the main grain source in a total mixed ration (TMR). In vitro rumen fermentation characteristics and microbes were assessed using two experimental diets. Diets included 33% dry matter (DM) of either corn (Corn TMR) or rice grains (Rice TMR). In a 48-h in vitro incubation, DM digestibility (IVDMD), neutral detergent fiber degradability (IVNDFD), crude protein digestibility (IVCPD), volatile fatty acids (VFAs), pH and ammonia nitrogen (NH 3-N) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Regarding the VFA composition, the proportion of butyrate was higher in the Rice TMR group than in the Corn TMR group. This differed with the findings of Yoo et al [ 10 ], who reported no difference in butyrate proportion between the rice TMR and corn TMR. Ha et al [ 24 ] reported that the normal range for butyrate is 80–150 mmol/mol; therefore, the butyrate proportion in the Rice TMR (149 mmol/mol) fell within the normal range.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the VFA composition, the proportion of butyrate was higher in the Rice TMR group than in the Corn TMR group. This differed with the findings of Yoo et al [ 10 ], who reported no difference in butyrate proportion between the rice TMR and corn TMR. Ha et al [ 24 ] reported that the normal range for butyrate is 80–150 mmol/mol; therefore, the butyrate proportion in the Rice TMR (149 mmol/mol) fell within the normal range.…”
Section: Discussioncontrasting
confidence: 99%
“…Yoo et al [ 10 ] observed no difference in CP digestibility between corn TMR and rice TMR, and they also found no significant difference in NH 3 -N concentration, which was positively correlated with CP digestibility. Similar to the findings of Yoo et al [ 10 ], our study showed no significant difference in NH 3 -N concentration between the groups fed with Corn TMR (7.12 mg/dL) and Rice TMR (7.33 mg/dL). Moreover, the ruminal NH 3 -N concentration in our study fell within the previously suggested optimal range for proper rumen fermentation (3.3 to 8.5 mg/dL) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations